Salivary cortisol responses of sports horses during a 4-days national show and the correlation to reactions in temperament tests - Munk Andersen, R.; Bovbjerg Jensen, R.; Palme, R.; Ejlersgaard, M. L.; Winther Christensen, J.; Munksgaard, L. (DCA Report; Nr. 044, 2014)
Sports horses are frequently stabled and exercised in novel environments in connection with competitions and shows. This environmental change typically leads to increased baseline cortisol levels, depending on how stressful the horse perceives the new environment. This study aimed to investigate: 1) baseline and post-exercise salivary cortisol concentrations during a 4-days national show, compared to the home environment and 2) whether baseline cortisol concentrations at the show reflected behavioural reactions and heart rate in temperament tests in the home environment. Fifty-two Danish warm-blood horses, selected for a national show, were used in this study (30 stallions, 10 mares, 12 geldings, age 3-10 years; mean 4.8 y). The horses were sampled for salivary cortisol on two consecutive days in their home environment and on days 2-4 during the show. Baseline samples were collected between 7-9, 12-14 and 17-19 h. Post-exercise samples were collected approximately 10 minutes after exercise and time of day for exercise was recorded. Two weeks before the show, two temperament tests were performed in the horses` home environment (moving object test (MO) and bridge test (BT)). Latency time (lat) to complete the tests, frequency of snorting (FS), average (HRavg) and peak heart rates (HRpeak) were recorded. As expected, baseline cortisol concentrations were higher (44-86%) at the show than at home and remained high throughout the show (Mixed models, mean±se, ng/ml, Day1 home: 0.97+0.66, Day 2 home: 1.13+0.78, Day 2 show: 1.49±1.13, Day 3 show: 1.75±1.09, Day 4 show: 1.96±1.39, P<0.001). Post-exercise levels were higher at the show than at home (mean±se, ng/ml, home: 1.65±1.23, show: 4.22±1.77, P<0.001). Cortisol baseline concentrations at the show correlated with reactions in the MO (Spearman; lat: r=0.36, P=0.018; FS: r=0.36, P=0.003; HRavg: r=0.32, P=0.041) and tended to correlate to the latency in the BT (r=0.32, P=0.055). Reactions in the MO test may have reflected fearfulness which in turn may predict reactions to stabling in a novel environment. The horses did not return to home baseline concentrations during the 4-days show, indicating that the period was too short for habituation to occur. LP: As expected, salivary cortisol was excreted at higher concentrations during a 4-days show compared to at home. Additionally, the reactions of horses in standardised temperament tests in the home environment do to some extent reflect their cortisol responses at the show. Horses that were tested more reactive likely perceived the show situation as more stressful.